GEOMORPHOLOGY AND KARSTIFICATION OF CARBONATE BUILD-UP IN CENTRAL LUCONIA PROVINCE, OFFSHORE SARAWAK - CHUNG, WEI KIAT (2017)
The advances in karsts have revolved on the studies of onshore outcrops, high-resolution multi-beam survey, and seismic. The research project aims to study the karstic morphology from a seismic viewpoint. The seismic data was provided by PETRONAS acquired over the Luconia shoals, offshore Sarawak. The carbonate platforms located over the shoals were developed over a rather tectonically active setting over a pre-rifted continental crust. Some platforms were documented to bloom as early as the late Oligocene period. The studied carbonate platform was developed over the southern field of the province, located north from the shores of Bintulu, Sarawak. The significant and rapid sea-level alternations during the Burdigalian to Serravallian stages highlighted several karstification periods with an extensive array of karst evidences observed on the platform. The high resolution seismic volume of the studied platform was applied with commercial attribute modules to enhance the karstic features captured from the seismic. The platform growth initiation started in a patchy trend during the Burdigalian before coalescing into a broad, flat-topped platform. One major karstification period was highlighted in the study. The sporadic paleo-cave collapse topography were correlated to the major sea-level drop. Two minor karstification periods were also identified. These periods were correlated to relatively short-lived sub-aerial events. The demise of the platform was related to the final surge of sea-level in the Serravallian, which inevitably drowned the platform. The studied platform eventually recorded up to four third-order sea-level cyclicity that spanned throughout the platform growth stages.